The Role of High Mobility Group Box 1 in Ischemic Stroke - Ye, Yingze; Zeng, Zhi; Jin, Tong; Zhang, Hongfei; Xiong, Xiaoxing; Gu, Lijuan (Frontiers in Cellular Neuroscience, 2019)
High-mobility group box 1 protein (HMGB1) is a novel, cytokine-like, and ubiquitous highly conserved nuclear protein that can be positively secreted by microglia or passively released by necrotic neurons. Ischemic stroke is a leading cause of death and disability worldwide, and the outcome is dependent on the amount of hypoxia-related neuronal death in the cerebral ischemic region. Acting as an endogenous danger-associated molecular pattern (DAMP) protein, HMGB1 mediates cerebral inflammation and brain injury, and participates in the pathogenesis of ischemic stroke. It is thought that HMGB1 signals via its presumed receptors, such as toll-like receptors (TLRs), matrix metalloproteinase (MMP) enzymes, and receptor for advanced glycation end products (RAGE) during ischemic stroke. In addition, the release of HMGB1 from the brain into the bloodstream influences peripheral immune cells. However, the role of HMGB1 in ischemic stroke may be more complex than this and has not yet been clarified. Here, we summarize and review the research into HMGB1 in ischemic stroke